Comparative analysis of the AE signals generated by partial single- and multi-source discharges - Cichoń, Andrzej; Boczar, Tomasz; Borucki, Sebastian; Lorenc, Marcin (Archives of Acoustics, 2007)
Within the research work carried out, the results of which are presented in this paper, a comparative analysis of the acoustic emission (AE) signals generated by partial single- and multi-source discharges (PDs) was carried out. The investigations were carried out in a model system, in which PDs were generated with two identical spark-gaps. In the work, spark-gaps in the surface system were used, due to the fact that this is the PD form occurring most often in power transformers. The AE signals were registered with a contact transducer placed on the external part of the tub. For the AE signals generated by both single-source PDs and multisource PDs, a frequency analysis using a fast Fourier transform (FFT) and an analysis in the time-frequency domain using a short-time Fourier transform (STFT) were carried out. The results of the frequency analysis are presented in the form of power density spectra, and the time-frequency analysis results in the form of spectrograms. Analyzing the research results the signals registered were compared from the point of view of identification possibilities of the particular PD forms. The aim of the research work carried out is also proving the usefulness of the AE method for diagnosing the condition of high-voltage power appliance insulation, in which multi-source discharges occur.